PENGARUH HARGA DAN PROMOSI TERHADAP PERILAKU KONSUMEN PRODUK SARI ROTI PADA MINIMARKET INDOMARET CABANG BOGOR 2 - Suherman, Agus; Arifin, Antoni Ludfi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The phenomenon that is used as the object of research is Price and Promotion of Consumer Behavior. This study aims to determine how much influence price and promotion have on consumer behavior. Data was collected using the Questionnaire and Literature Study technique. The research method used is the method of quantitative analysis. The population in this study are consumers who make purchases of Sari Roti products at the Indomaret Minimarket Bogor Branch 2, with a research sample of 155 respondents. The results of the study found: a) Price (X1) has a significant influence on consumer behavior of 0.434. This means that there is a relationship between the X1 variable that will affect the Y variable, which is 43.4%; b) Promotion (X2) has a significant influence on consumer behavior of 0.679. This means that the X2 variable will affect the Y variable in the amount of 69.7%; and c) Price (X1) and Promotion (X2) have a significant effect simultaneously on the Consumer Behavior of Sari Roti Products at Indomaret Bogor Branch 2 of 0.705. This means that the variable Price (X1) and Promotion (X2) together with Consumer Behavior (Y) is 0.705. This value reflects that the relationship between Price (X1) and Promotion (X2) together with Consumer Behavior (Y) qualitatively has a very strong and positive relationship of 70.5%.